Obtaining Fat-Soluble Pigments—Carotenoids from the Biomass of Chlorella Microalgae - Julia Bazarnova; Yulia Smyatskaya; Antonina Shlykova; Aleksei Balabaev; Saša Đurović (Applied Sciences, 2022)
The aim of this study was to use a directed mode of cultivation of the microalgae Chlorella for biomass production, followed by the subsequent extraction of carotenoids. The effect of a stress inducer of carotenogenesis (hydrogen peroxide) and a growth stimulator (pyridoxine, vitamin B6) on the accumulation of photosynthetic pigments by the biomass of the microalga C. vulgarisBIN in the process of directed cultivation was studied. It was revealed that the combination of these additives in the culture medium increases the content of chlorophylls and carotenoids in the biomass twofold compared to the control sample. The preliminary activation of the biomass by high-speed ultra-homogenization (a rotor rotation range from 6000 to 12,000 rpm) was also investigated. Using ultrasound extraction, the pigment complex was isolated from the activated biomass. The saponification and subsequent neutralization of carotenoids were carried out in an inert medium. The resulting sample contained carotenoids in the amount of 52 ± 3 mg/mL. The chemical profile of the carotenoids in the biomass of the microalga Chlorella vulgaris BIN was also established. The major carotenoid was lutein (45%), followed by fucoxanthin (12%) and β-carotene (4.3%). The oil extract of the carotenoids may be used for the further production of a microencapsulated product with the aim of targeted delivery to the lower parts of the gastrointestinal tract.